학령 후기 아동의 실행기능과 학교적응: 자기효능감의 매개효과 - 정재은(Jae Eun Jeong); 신나나(Nana Shin) (Korean Journal of child studies, 2019)
Objectives: The main purpose of this study was to examine the mediating effect of self-efficacy on the relationship between executive function (i.e., inhibition, working memory, and shifting) and school adjustment in upper elementary school students. Methods: A total of 69 upper elementary school students participated in this study. They responded to questions regarding their perceived self-efficacy and school adjustment, and in addition, three tasks of executive function were administered: Stroop color and word test, digit span test, and trail making test. Results: The subjects’ perceived self-efficacy was found to partially mediate the relationship between their ability to inhibit and shift and school adjustment. However, the relationship between working memory and school adjustment was not mediated by self-efficacy. Conclusion: This study highlights the importance of executive function and self-efficacy on school adjustment during the upper elementary school period. Findings from this study may be useful for the development of a self-efficacy enhancement program for upper elementary school students. KCI Citation Count: 9